Leaf structure and defence control litter decomposition rate across species and life forms in regional floras on two continents - CORNELISSEN, JOHANNES H. C.; PÉREZ-HARGUINDEGUY, NATALIA; DÍAZ, SANDRA; GRIME, J. PHILIP; MARZANO, BARBARA; CABIDO, MARCELO; VENDRAMINI, FERNANDA; CERABOLINI, BRUNO (The New phytologist, 1999)
There is some evidence that traits of fresh leaves that provide structural or chemical protection (‘defence’) remain operational in the leaf litter and control interspecific variation in decomposition rate in or on the soil. We tested experimentally whether the negative relationship between foliar defence and litter decomposition rate is fundamental, i.e. whether it is seen consistently across higher plant species and life forms, and whether it is repeated in the floras of geographically and climatically distinct areas separated by an ocean. We employed the published results of two outdoor litter bag experiments, in which we simultaneously compared the relative mass losses (‘decomposibility’) of leaf litters of a wide range of plant species. One experiment was in Córdoba, Argentina, and included 48 Argentine species typical of the dry, subtropical landscapes along a steep altitudinal gradient. The other was in Sheffield, UK, and hosted 72 British species typical of the temperate–Atlantic landscape there. We linked the two experiments through a similar experiment in Sheffield that hosted litters of subsets of both the Argentine and British species. We also tested fresh leaves of all species from the same areas for tensile strength (‘toughness’) and relative palatability to generalist herbivorous snails in multi-species ‘cafeteria’ experiments. Both in Argentina and in Great Britain there were highly significant correlations between leaf palatability (r=0.61; 0.73) or leaf tensile strength (r=−0.60; −0.60) and litter mass loss across all species. These relationships could be explained by variation both between and within broad life-form groups. Specific leaf area (area[ratio ]dry mass) of fresh leaves was consistently correlated only with litter mass loss within British life form groups. We illustrated the possible ecosystem consequences of these relationships by comparing functional traits of British species differing in leaf habit. In comparison with deciduous species, evergreens generally had innately slow growth, which corresponded to their longer-lived leaves of lower specific leaf area, higher tensile strength and lower palatability to generalist invertebrate herbivores. Correspondingly, evergreens produced more resistant leaf litter. Thus, slow-growing evergreens might maintain their position in infertile ecosystems through leaf traits that help them to conserve their nutrients efficiently and to keep nutrient mineralization low, thereby not allowing potentially fast-growing deciduous species to outcompete them.